2019
DOI: 10.1021/acs.biomac.9b01057
|View full text |Cite
|
Sign up to set email alerts
|

Filament Rigidity Vies with Mesh Size in Determining Anomalous Diffusion in Cytoskeleton

Abstract: The diffusion of microscopic particles through the cell, important to processes such as viral infection, gene delivery, and vesicle transport, is largely controlled by the complex cytoskeletal network, comprised of semiflexible actin filaments and rigid microtubules, that pervades the cytoplasm. By varying the relative concentrations of actin and microtubules, the cytoskeleton can display a host of different structural and dynamic properties that, in turn, impact the diffusion of particles through the composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 64 publications
6
51
0
Order By: Relevance
“…To provide another independent measure of dynamics to complement our DDM results, we perform particle-tracking analysis as described in the Methods. We compute mean-squared This exponent is similar to that reported previously for similar actin-microtubule networks 36 .…”
Section: Particles Exhibit Both Subdiffusion and Ballistic Transport supporting
confidence: 55%
See 1 more Smart Citation
“…To provide another independent measure of dynamics to complement our DDM results, we perform particle-tracking analysis as described in the Methods. We compute mean-squared This exponent is similar to that reported previously for similar actin-microtubule networks 36 .…”
Section: Particles Exhibit Both Subdiffusion and Ballistic Transport supporting
confidence: 55%
“…DDM is useful for investigating diffusive and active dynamics of soft materials such as those found in biological systems 32 , including cytoskeleton complexes [33][34][35] . In our own previous work, we have used DDM to study the passive transport of tracers within static actin-microtubule networks, and found that these networks exhibit subdiffusive behavior 36 . Here, we first use DDM analysis to generate image structure functions ( , ) at varying wavenumbers , as described in the Methods.…”
Section: Microtubules Slow Actomyosin Activity 7-foldmentioning
confidence: 99%
“…At high collagen concentration, the large rigidity of the collagen fibers likely contributes a caging effect, consistent with a previous study on composite networks of semiflexible actin and rigid microtubules. 46 In the composite network, the confining agent (hyaluronan) is much softer than collagen, but the mesh size is much smaller. Interestingly, we do not observe subdiffusive motion in a pure hyaluronan system at 4 mg mL À1 , suggesting the need of an elastically active element to induce subdiffusion.…”
Section: Discussionmentioning
confidence: 99%
“…The mesh size of the composite networks was calculated as a geometrical average of the mesh sizes of the hyaluronan and collagen networks: 46 j c À3 = (j HA À3 + j coll À3 ),…”
Section: Mesh Size Determinationmentioning
confidence: 99%
See 1 more Smart Citation